Burden of Care among Mothers Having Children with Thalassemia - Bhujel, Bishnu; Adhikari Mishra, Tulashi; Bhujel, Bishnu (Journal of Institute of Medicine Nepal, 2022)
Introduction Thalassemia is a blood related genetic disorder in which body makes an abnormal form or inadequate amount of hemoglobin. Though care giving is a normal parental duty, providing lifelong caring process may increase burden among parents especially mothers. The aim of this study was to assess the level of burden of care among mothers having children with thalassemia. Methods This descriptive cross-sectional study was carried out among 100 mothers attending a Thalassemia day care center in Kathmandu, Nepal. Non-probability purposive sampling technique was used to collect data through interview using Zarit Burden Interview scale. Results Out of 100 mothers, 19% had little or no burden, 43% had mild level of burden of care, 34% had moderate burden of care and 4% had severe burden of care. Forty three percent of the mothers frequently felt that child is depended upon her, 20% of the mothers, frequently felt stressed from caring their children. 35% of the mothers frequently felt that money is insufficient to care for their child. Statistically significant association was found between level of burden with economic status (0.002) and place of residence (0.03). Conclusion The study concludes that mothers face burden of caring the child having thalassemia. Burden of care among mothers tends to be influenced by the family economic status and residence. This burden should be minimized by health personnel through proper counseling and support to mothers of thalassemic children.